Three new species of Mitracarpus Zucc. (Rubiaceae) from Brazil - Cabral, Elsa Leonor (2013)
Three new species of Mitracarpus Zucc. (Rubiaceae), Mitracarpus carajasensis E. L. Cabral, Sobrado & E. B. Souza, Mitracarpus federalensis E. L. Cabral, Sobrado & E. B. Souza and Mitracarpus fernandesii E. L. Cabral, Sobrado & E. B. Souza, from Brazil, are described, illustrated and compared to related taxa.